AGENDA IS YOUR JOB MAKING YOU SICK? A CONFERENCE ON INDOOR AIR QUALITY IN FEDERAL AND D.C. GOVERNMENT BUILDINGS WEDNESDAY, 19890301 (Tufts Archival Research Center, 2007)
Agenda for Safe Workplace Air Coalition conference on indoor air quality (IAQ) in federal and D.C. government buildings. Includes presentations by labor representatives, scientists, and air quality consultants, in addition to industry representatives. Also includes presentation by Congressman Tom McMillen and case study of USIA.